Comprehensive phenotypic analysis of multiple gene deletions of α-glucan synthase and Crh-transglycosylase gene families in Aspergillus niger highlighting the versatility of the fungal cell wall - Katharina J. Ost; Mark Arentshorst; Bruno M. Moerschbacher; Mareike E. Dirks-Hofmeister; Arthur F.J. Ram (The Cell Surface)
Multiple paralogs are found in the fungal genomes for several genes that encode proteins involved in cell wall biosynthesis. The genome of A. niger contains five genes encoding putative α-1,3-glucan synthases (AgsA-E) and seven genes encoding putative glucan-chitin crosslinking enzymes (CrhA-G). Here, we systematically studied the effects of the deletion of single (agsA or agsE), double (agsA and agsE), or all five ags genes (agsA-E) present in A. niger. Morphological and biochemical analysis of ags mutants emphasizes the important role of agsE in cell wall integrity, while deletion of other ags genes had minimal impact. Loss of agsE compromised cell wall integrity and altered pellet morphology in liquid cultures.Previous studies have indicated that deletion of all crh genes in A. niger did not result in cell wall integrity-related phenotypes. To determine whether the ags and crh gene families have redundant functions, both gene families were deleted using iterative CRISPR/Cas9 mediated genome editing. The 12-fold deletion mutant was viable and did not exhibit growth defects under non-stressing growth conditions. A synergistic effect on cell wall integrity was observed in this 12-fold deletion mutant, particularly when exposed to cell wall-perturbing compounds. The cell wall composition, extractability of glucans by alkali, and scanning electron microscopy analysis showed no differences between the parental strain and mutants lacking ags genes, crh genes, or both. These observations underscore the ability of fungal cells to adapt and secure cell wall integrity, even when two entire cell wall protein-encoding gene families are missing.